Novel rearranged and highly oxygenated abietane diterpenoids from the leaves of Tripterygium wilfordii. Issue 10 (4th March 2015) - Ni, Lin; Ma, Jie; Li, Chuang-jun; Li, Li; Guo, Jia-mei; Yuan, Shao-peng; Hou, Qi; Guo, Ying; Zhang, Dong-ming
Graphical abstract: Highlights: Triptergulides A–D have not been previously reported as natural products. Triptergulides A and B were novel rearranged abietane diterpenes. Compounds5 –7 exhibited inhibitory effects on HIV-1 replication. Five compounds demonstrated inhibitory effects on nitric oxide production. Abstract: Two novel rearranged abietane diterpenes, triptergulide A (1 ) containing a fused 5/6/6/3/6/4 hexacyclic system and triptergulide B (2 ), possessing both 7/12 and 13/14 oxygen bridges, and two new 18(4→3)- abeo -abietanes, triptergulides C and D (3 –4 ), together with three known diterpenoids (5 –7 ) were isolated from the leaves of Tripterygium wilfordii . Among these compounds, compounds5 –7 exhibited inhibitory effects on HIV-1 replication with an IC50 range of 0.027–0.98 μM. Compounds1, 2, 5, and6 demonstrated inhibitory effects that were similar to the inhibitory effects of dexamethasone on nitric oxide production in LPS-induced macrophages at a concentration of 10 μM in an in vitro bioassay.